PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI GURU DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN PAMULANG KOTA TANGERANG SELATAN - Mastanah Mastanah; Saiful Anwar; Siti Zubaidah (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the effects of principals’ transformational leadership, teacher motivation, and interpersonal communication on the performance of public elementary school teachers in Pamulang District, South Tangerang City, both directly and through teacher motivation as a mediating variable. Methods: The study employed a quantitative approach using a survey method. The research sample consisted of 120 teachers selected through purposive sampling. Data were collected using questionnaires and analyzed through path analysis. Results: The findings indicate that transformational leadership, teacher motivation, and interpersonal communication have positive and significant effects on teacher performance. Transformational leadership and interpersonal communication also have positive and significant effects on teacher motivation. Teacher motivation shows the strongest direct effect on teacher performance and functions as a mediator in the relationship between transformational leadership, interpersonal communication, and teacher performance. The research model explains a substantial proportion of the variance in teacher performance. Novelty: The novelty of this study lies in examining the mediating role of teacher motivation within an integrated model that links transformational leadership and interpersonal communication to teacher performance